2013
DOI: 10.1530/joe-13-0282
|View full text |Cite
|
Sign up to set email alerts
|

UII and UT in grouper: cloning and effects on the transcription of hormones related to growth control

Abstract: Urotensin II (UII) is a cyclic peptide that was originally extracted from the caudal neurosecretory system (CNSS) of fish. UII is well known to exhibit cardiovascular, ventilatory, and motor effects in vertebrates. Studies have reported that UII exerts mitogenic effects and can act as an autocrine/paracrine growth factor in mammals. However, similar information in fish is limited. In this study, the full-length cDNAs of UII and its receptor (UT) were cloned and characterized in the orange-spotted grouper. UII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
0
19
0
2
Order By: Relevance
“…Immunohistochemical labeling has confirmed that UII is primarily located in neurosecretory cells of the ventral spinal cord (Owada et al, 1985;Oka et al, 1989;Parmentier et al, 2006). However, subsequent studies have shown that UII is also present in the fish brain (Waugh and Conlon, 1993), and the expression of UII mRNA in fish brain has been confirmed by reverse-transcription polymerase chain reaction (RT-PCR; Lu et al, 2006;Sun et al, 2014). In various species of freshwater and seawater fish, UII is found in cerebrospinal fluid (CSF)-contacting neurons located within the ventral ependyma bordering the central canal along the entire length of the spinal cord and medulla Lederis 1986, 1988).…”
Section: F the Urotensin II And Urotensin Ii-related Peptide Genesmentioning
confidence: 99%
See 3 more Smart Citations
“…Immunohistochemical labeling has confirmed that UII is primarily located in neurosecretory cells of the ventral spinal cord (Owada et al, 1985;Oka et al, 1989;Parmentier et al, 2006). However, subsequent studies have shown that UII is also present in the fish brain (Waugh and Conlon, 1993), and the expression of UII mRNA in fish brain has been confirmed by reverse-transcription polymerase chain reaction (RT-PCR; Lu et al, 2006;Sun et al, 2014). In various species of freshwater and seawater fish, UII is found in cerebrospinal fluid (CSF)-contacting neurons located within the ventral ependyma bordering the central canal along the entire length of the spinal cord and medulla Lederis 1986, 1988).…”
Section: F the Urotensin II And Urotensin Ii-related Peptide Genesmentioning
confidence: 99%
“…The 222 UII gene is also expressed in flounder and grouper endocrine glands, including pituitary, head kidney (where the interrenal tissue is located), and ovary (Lu et al, 2006;Sun et al, 2014).…”
Section: H Distribution Of Urotensin II and Urotensin Ii-related Pepmentioning
confidence: 99%
See 2 more Smart Citations
“…Double-immunofluorescence labeling in mouse brain revealed a co-localization of URP and GNRH in fibers in the median eminence and vascular organ of the lamina terminalis as well as in cell bodies in the preoptic area, suggesting that URP is co-released with GNRH (Egginger et al 2011). In the orange-spotted grouper (Epinephelus coioides), UII may promote growth through the activation of GHRH expression and inhibition of SS1 and SS2 concentrations in the hypothalamus, which stimulates GH expression in the pituitary and increases GH receptor expression (Sun et al 2013).…”
Section: Uts2r5mentioning
confidence: 99%